Teaching innovation in an age of disruption. (31st May 2021) - Kresta, Suzanne M.
Abstract: In a climate of global disruptions, it seems certain that adaptive change will be an important part of our lives for the foreseeable future. Now, more than ever, we have a responsibility to introduce our students to skills that will support them in this work. This paper is a synthesis of a number of invited plenary talks given from 2014–2019 which explore the dichotomy of engineering: we are innovators and problem solvers who also hold reliability and protection of the public as our most important obligation. The data show that innovation will become more important in the decades ahead, but finding academics who love the uncertainty that comes with teaching design is becoming more difficult. The tension—and occasional polarization—between prioritizing innovation or maintaining reliable known solutions is deconstructed and explored. Two examples of how this plays out in industry are presented. The second half of the paper presents a selection of important ideas for teaching innovation thinking. Practical teaching strategies are included for easy implementation in the classroom. In closing, the major threads in (engineering) teaching and learning research are summarized, again, with samples of best practices in the context of teaching collaborative innovation. The goal of this paper is to provide engineering instructors with tools which are easily applied to build curiosity and an innovation mindset, without reducing their commitment to reliable and robust engineering problem solving. Abstract : Teaching innovation skills in engineering classrooms can be done in a way that also respects our values of reliable outcomes and protection of the public good. Proven first steps to expand our impact in each of the categories in this schema are provided, along with industrial context and examples.